Medication usage, patient health practices, and healthcare accessibility in the community of Tirrases, San Jose, Costa Rica (UNED Research Journal, 2017)
A survey regarding medication use and health care accessibility was distributed to residents of the urban marginalized community of Tirrases, San Jose, Costa Rica. Individual interviews were conducted with selected patients and medical practitioners to add detail and perspective to the survey responses. One hundred and ninety four individuals responded to the survey, and five individuals were interviewed, four patients and one medical practitioner. Sixteen percent of the surveyed population did not have medical insurance, and comparisons between insured and uninsured populations showed that the uninsured population reported lower levels of chronic illness, use of medication prescribed by doctors, anddecreased frequency of doctor visits. Patients were comfortable overall discussing their medications with their doctors, and the majority used natural medicine. Medical practitioners should be made aware of these medication habits and patient responses to better design patient treatment plans and make medical care and clinic services more accessible for both insured and uninsured patients.
Keywords: Medication Use; Access to Medical Care; Chronic Illness; Urban Marginalized Community; Healthcare; Natural Medicine; Insurance